2010
DOI: 10.1007/s10637-010-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study evaluating causality attribution for serious adverse events during early phase oncology clinical trials

Abstract: Attributing causality to SAE's is a complex process. Clinical trial researchers apply a logical system of reasoning, but feel that the current method of assigning causality could be improved. Based on these findings, future research involving the development of a new causality assessment tool specifically for use in early phase oncology clinical trials may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Nevertheless, there was high predictive ability for phase I trials to identify clinically relevant toxicities. Attribution of toxicities to experimental agents is also not straightforward in phase I trials and errors are frequent in early trials (18). Interestingly, toxicities easily attributable to experimental drugs, such as hand-foot syndrome, neurotoxicity, peripheral neuropathy, neutropenia, and mucositis, were most concordant when comparing top 3 grade 3 and 4 toxicities between early and later trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was high predictive ability for phase I trials to identify clinically relevant toxicities. Attribution of toxicities to experimental agents is also not straightforward in phase I trials and errors are frequent in early trials (18). Interestingly, toxicities easily attributable to experimental drugs, such as hand-foot syndrome, neurotoxicity, peripheral neuropathy, neutropenia, and mucositis, were most concordant when comparing top 3 grade 3 and 4 toxicities between early and later trials.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests reluctance on the part of treating physicians to more definitely attribute a particular toxicity as drug related, even when the impact at the study level (ie, in what constitutes a DLT) would be the same. This finding may also reflect caution on the part of physicians; when physicians are uncertain about drug causality, they may call it ‘possibly’ related for safety reasons, knowing that ‘possibly’ related will ultimately be counted as related by standard clinical convention on Phase I studies [12]. By comparison, similar numbers of toxicities were attributed as ‘unrelated’ (27%) and ‘unlikely’ (27%) related, suggesting that physicians are not similarly hesitant to definitely attribute toxicities as unrelated to the study drug.…”
Section: Discussionmentioning
confidence: 99%
“…When a patient on a clinical trial experiences a DLT or a serious adverse event, the investigator must determine whether the event is attributable to the investigational drug or not. A recent qualitative study evaluating causality assessment during early-phase oncology trials found that it is a complex process, often without complete clinical and investigational data available to the investigator [26]. In early-phase oncology clinical trials (phase I), the toxicities of the study medication are frequently not well characterized, and often occur in the context of advanced cancer and multiple co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…It is not always possible to assess the contributions of a new agent to toxicity. Investigators may follow a “precautionary principle” and err on the side of caution by attributing the toxicity to the study drug [26]. That a potentially active new agent is labeled toxic and not studied further, is a risk taken in order to assure patient safety.…”
Section: Discussionmentioning
confidence: 99%